2022
DOI: 10.2967/jnumed.122.264104
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Posttreatment68Ga-PSMA-11 PET/CT and18F-FDG PET/CT in Metastatic Castration-Resistant Prostate Cancer Treated with177Lu-PSMA-617 and NOX66 in a Phase I/II Trial (LuPIN)

Abstract: BACKGROUND 177 Lutetium PSMA-617 ( 177 LuPSMA-617) therapy has shown high prostate specific antigen (PSA) response rates in men with metastatic castration-resistant prostate cancer (mCRPC). However early treatment resistance is common. This LUPIN substudy aimed to determine the prognostic value of post-treatment quantitative PET for PSA progression free (PSA-PFS) and overall survival (OS) with 177 LuPSMA-617 therapy. METHODS56 men with progressive mCRPC were enrolled in LuPIN trial and received up to 6 doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The majority of patients receiving PSMA-targeted peptide receptor radionuclide therapy will get a drop in PSMA intensity, which is not predictive of OS. 12,17 However, these results suggest the depth of the reduction in SUVmax and SUVmean may be a proxy marker of radiation sensitivity and depth of cell death achieved. Currently, while we can measure PSMA characteristics at baseline to predict treatment response, we do not have an easy measure of radiation sensitivity, which is a significant factor in treatment resistance with 177 LuPSMA.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The majority of patients receiving PSMA-targeted peptide receptor radionuclide therapy will get a drop in PSMA intensity, which is not predictive of OS. 12,17 However, these results suggest the depth of the reduction in SUVmax and SUVmean may be a proxy marker of radiation sensitivity and depth of cell death achieved. Currently, while we can measure PSMA characteristics at baseline to predict treatment response, we do not have an easy measure of radiation sensitivity, which is a significant factor in treatment resistance with 177 LuPSMA.…”
Section: Discussionmentioning
confidence: 94%
“…Currently, while we can measure PSMA characteristics at baseline to predict treatment response, we do not have an easy measure of radiation sensitivity, which is a significant factor in treatment resistance with 177 LuPSMA. 17,18 Treatment failure in RG 3 is likely due at least in part to a combination of both baseline PSMA heterogeneity/intensity and low radiation sensitivity. We can measure PSMA heterogeneity and expression at baseline (SUVmean), but the Δ Lu-SPECT parameters at 6 weeks may give some additional indication of radiation sensitivity, and this warrants further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…the FPQ, predicted lesional response to PSMA-targeted RLT, aligns with the findings of a number of studies suggesting predictive and prognostic power in prostate cancer of the [ 18 F]FDG SUV max of a lesion or of the total tumor burden. These studies showed these variables to be associated with negative disease characteristics and poor patient outcomes [19][20][21][38][39][40] , including in men with mCRPC 18,22,41,42 , and those undergoing PSMA-targeted RLT 25,29 . Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…As on many other malignant cell types, GLUT1 overexpression on prostate cancer cells is reflected by uptake of the fluorine-18-conjugated glucose analogue fluorodeoxyglucose ([ 18 F]FDG), shown on PET 19 . Higher [ 18 F]FDG uptake now is well-recognized to correlate with prognosticallyunfavorable pathological factors in prostate cancer in general 20,21 , and with poor outcomes in men receiving systemic treatment of mCRPC, including PSMA-targeted RLT 18,[22][23][24][25] . As a result, [ 18 F]FDG PET/computed tomography (CT) increasingly is being applied in mCRPC, to provide prognostic and/or predictive data 3,16,[26][27][28][29] .…”
mentioning
confidence: 99%
“…Ga-68-PSMA-11 (Ga 68 PSMA-11) was FDA-approved in 2020, followed by F-18-piflufolastat (Pylarify) in 2021. Subsequently, Lu-177-PSMA-617 (Pluvicto) was approved in March 2022 for therapeutic applications [18,19]. PSMA-617 targets PSMA and becomes internalized into cancer cells [20].…”
Section: Radiotheranosticsmentioning
confidence: 99%